The role of cardiac magnetic resonance in MINOCA diagnosis. (14th October 2021) - Dias Claudio, F; Picarra, B; Neves, D; Trinca, M
Abstract: Introduction: Absence of obstructive coronary disease does not imply absence of acute myocardial infarction (AMI). Hence, it can be designated as Myocardial Infarction with Non-obstructive Coronary Arteries (MINOCA). Performing Cardiac Magnetic Resonance (CMR) can be essential for establishing a final diagnosis, according to the presence and pattern of late gadolinium enhancement (LGE). Purpose: The aim of this study is to evaluate the diagnostic and prognostic impact of CMR in patients with a possible diagnosis of MINOCA. Methods: A 7-year prospective study, which included all patients proposed to CMR with a presumptive diagnosis of MINOCA due to acute chest pain, troponin raise and absence of angiographically significant coronary disease (luminal stenosis of <50%). All patients performed functional, anatomical evaluation and LGE assessment. We analysed clinical characteristics, electrocardiographic presentation, echocardiographic and invasive coronary angiography results. A presumptive diagnosis was elaborated after invasive coronary angiography and comparison was made with the definitive one after CMR. Results: A total of 96 patients were included, 50% were male, with a mean age of 48±20 years old. Clinical history of hypertension was observed in 51.0% patients, 35.4% had dyslipidaemia, 7.3% with diabetes, obesity was present in 22.9% of patients and smoking habits in 30.2%. At admission, 44.8% had ST segment elevation, so emergent invasive coronary angiography was performed. The mean highest troponin I was 7.34±9.18 ng/mL. Late gadolinium enhancement was observed in 53 (55.2%) of patients. After CMR realization a final diagnosis of MINOCA was made in only 8 patients (8.4%) and in 51 patients (53.1%) CMR evaluation allowed a diagnosis modification, with impact on patients' management and prognosis. A definitive diagnosis of myocarditis was seen in 46.9% (n=45) of cases, of Takotsubo's myocardiopathy in 13.5% (n=13), and hypertrophic cardiomyopathy in 3.1% (n=3). In 27 (28.1%) of patients, late gadolinium enhancement was not found. This diagnosis adjustment had an impact on treatment in 34.4% (n=33). Conclusion: CMR is a pivotal technique on MINOCA patients' management. Our study portrayed the importance of performing CMR, allowing initial diagnosis modification in half of the cases, with important therapeutic in one third of patients and prognostic implications, related to diagnosis and target treatment adverse effects. FUNDunding Acknowledgement: Type of funding sources: None.